Research ethics for counsellors, nurses and social workers - Danchev, Dee; Ross, Alistair, 1957- (Los Angeles : SAGE, 2014)
Designed to help students make the best start in their research career, this high practical step-by-step guide considers the ethical implications which arise at each stage of the research process and provides students with the tools they need to become confident, skilled researchers.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Psychology -- Research -- Moral and ethical aspects; Social service -- Research -- Moral and ethical aspects; Medicine -- Research -- Moral and ethical aspects